2000
DOI: 10.1097/00002030-200005260-00010
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy on Kaposi's sarcoma of highly active antiretroviral therapy in a cohort of HIV-positive patients

Abstract: HAART appears to have prolonged efficacy on AIDS-KS, even without specific KS therapy, and this effect appears to be linked to the restoration of immune function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
69
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 22 publications
11
69
0
Order By: Relevance
“…However, we had the opportunity to examine both risk factors for KS and clinical outcomes among patients predominantly treated with NNRTI-based regimens in a KS endemic country. The fact that regression rates in our study are similar to those published for industrialized countries, where clinical responses range from 67 to 85% [8,9], should be somewhat reassuring to patients and physicians who do not have easy access to specific anti-neoplastic therapy or PI-based HAART regimens. Less than half of the patients in this study were able to access any chemotherapy for KS, and only four completed a full course of treatment, which suggests that NNRTI-based HAART may be adequate therapy for most patients who develop KS when starting or while receiving HAART.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…However, we had the opportunity to examine both risk factors for KS and clinical outcomes among patients predominantly treated with NNRTI-based regimens in a KS endemic country. The fact that regression rates in our study are similar to those published for industrialized countries, where clinical responses range from 67 to 85% [8,9], should be somewhat reassuring to patients and physicians who do not have easy access to specific anti-neoplastic therapy or PI-based HAART regimens. Less than half of the patients in this study were able to access any chemotherapy for KS, and only four completed a full course of treatment, which suggests that NNRTI-based HAART may be adequate therapy for most patients who develop KS when starting or while receiving HAART.…”
supporting
confidence: 83%
“…KS was an uncommon diagnosis among HIV-infected individuals initiating HAART in rural Uganda, affecting 3.2% of individuals in this study and having an estimated inci- [8,9], Nevertheless, mortality associated with KS in our study was very high (30% compared with 11% for participants without KS). Our findings are similar to those of a recently reported study from South Africa which found a prevalence of KS of 3.4% among unselected patients in an HIV clinic population and a mortality rate of 25% [12].…”
Section: Discussionmentioning
confidence: 59%
“…Two studies have shown a correlation between KS remission and a high CD4 cell count or a strong increase in the CD4 cell count. Dupont et al (2000) found that an increase in the CD4 cell count of more than 150 Â 10 6 l À1 after 12 months of HAART was predictive of complete remission from KS at month 24 in HIV-infected patients. Similarly, Cattelan et al (1999) found a positive correlation between the CD4 cell count and KS control during antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 91%
“…10 These findings may be attributable both to specific cancer characteristics in HIV-infected individuals (a more aggressive behavior and an advanced stage at diagnosis) [6][7][8]11,12 and to subject characteristics (immunodeficiency, low performance status). The use of HAART improved short-and medium-term survival in HIV-infected patients with cancer, 8 especially those with ADM [13][14][15] and some types of NADM (e.g., HD) 16,17 and reduced the difference from the general population. 8 However, very few studies described 10-year survival in patients with HIV and cancer, and the only published data are limited to subjects with NHL, Kaposi's sarcoma (KS), and anal cancer.…”
mentioning
confidence: 99%